1989
DOI: 10.1007/bf03010768
|View full text |Cite
|
Sign up to set email alerts
|

Haemodynamic effects of atropine during halothane or isoflurane anaesthesia in infants and small children

Abstract: In this study, two-dimensional and pulsed Doppler echocardiography were used to measure cardiovascular changes before and after IV atropine in 31 infants and small children during halothane (n = 15) In children (mean age 6 yrs) IV atropine administered during halothane and nitrous oxide anaesthesia increased cardiac output (CO). t In previous studies of infants who received PO or IM atropine premedieation, heart rate (HR) and mean blood pressure (MBP) have been reported to be greater than during halothane an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…Similar to prior studies in infants and small children, the increased heart rate after atropine increased cardiac output but did not attenuate myocardial depression as measured by ejection fraction and stroke volume in either neonates or infants (30). The increased heart rate did not compensate for decreased stroke volume, and cardiac output remained depressed from awake levels in both neonates and infants.…”
Section: Hemodynamic Depression During Anesthesia In Neonates and Infsupporting
confidence: 77%
“…Similar to prior studies in infants and small children, the increased heart rate after atropine increased cardiac output but did not attenuate myocardial depression as measured by ejection fraction and stroke volume in either neonates or infants (30). The increased heart rate did not compensate for decreased stroke volume, and cardiac output remained depressed from awake levels in both neonates and infants.…”
Section: Hemodynamic Depression During Anesthesia In Neonates and Infsupporting
confidence: 77%
“…Anaesthesia influences CO in more than one way; preload, afterload and contractility are all affected as well as heart rate, whereas changes in mean airway pressure are considered to have a more selective effect on preload. Murray et al 212 showed an increase in heart rate and cardiac output but not stroke volume of atropine. Their study also showed that the anaesthesia with halothane and isoflurane, before atropine was given, gave a decrease in both CO and stroke volume compared to preanaesthesia values.…”
Section: Stroke Volume Heart Rate and Cardiac Output (Paper Ii)mentioning
confidence: 96%
“…The failure of atropine to increase f H was unexpected, particularly given the marked effects on the pulmonary circulation that also obey an inhibitory vagal influence (Burggren, 1975), and may be attributed to the isoflurane anaesthesia. It is possible that the direct cardio-depressive effect of isoflurane may have lowered the EF (Housmans et al, 2000;Murray et al, 1989). Alternatively, or in addition, isoflurane may have reduced the afterload (through arterial hypotension), which could increase EF compared with that in conscious tortoises, given the steep negative relationship between V s and afterload in chelonians (Farrell et al, 1994;Joyce et al, 2016).…”
Section: Resultsmentioning
confidence: 99%